An atomic detail model for the human ATP binding cassette transporter P-glycoprotein derived from disulfide cross-linking and homology modeling. - Stenham, DR; Campbell, J; Sansom, MS; Higgins, C; Kerr, I; Linton, K (2003)
The multidrug resistance P-glycoprotein mediates the extrusion of chemotherapeutic drugs from cancer cells. Characterization of the drug binding and ATPase activities of the protein have made it the paradigm ATP binding cassette (ABC) transporter. P-glycoprotein has been imaged at low resolution by electron cryo-microscopy and extensively analyzed by disulphide cross-linking, but a high resolution structure solved ab initio remains elusive. Homology models of P-glycoprotein were generated using the structure of a related prokaryotic ABC transporter, the lipid A transporter MsbA, as a template together with structural data describing the dimer interface of the nucleotide binding domains (NBDs). The first model, which maintained the NBD:transmembrane domain (TMD) interface of MsbA, did not satisfy previously published cross-linking data. This suggests that either P-glycoprotein has a very different structure from MsbA or that the published E. coli MsbA structure does not reflect a physiological state. To distinguish these alternatives, we mapped the interface between the two TMDs of P-glycoprotein experimentally by chemical cross-linking of introduced triple-cysteine residues. Based on these data, a plausible atomic model of P-glycoprotein could be generated using the MsbA template, if the TMDs of MsbA are reoriented with respect to the NBDs. This model will be important for understanding the mechanism of P-glycoprotein and other ABC transporters.